2002
DOI: 10.4269/ajtmh.2002.66.777
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between active and inactive neurocysticercosis by metacestode excretory/secretory antigens of Taenia solium in an enzyme-linked immunosorbent assay.

Abstract: Abstract. To detect IgG antibodies to Taenia solium, a controlled double-blind study was conducted using 91 coded cerebrospinal fluid samples from patients with neurocysticercosis (NCC) and other neurologic disorders. Samples were tested in an enzyme-linked immunosorbent assay (ELISA) using metacestode excretion/secretion antigens. The results were correlated with data from medical records on the diagnosis of NCC (based on computed tomography and magnetic resonance imaging criteria) and other neurologic disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 35 publications
2
33
0
6
Order By: Relevance
“…[3,4] We have used membrane antigen of cysticercus fasciolaris (larval stage of Taenia taeniaeformis pathogenic in rat) in anti-IgG and anti-IgM ELISA for the immunodiagnosis of NC. [5] In the current study, we have designed and evaluated a Dot ELISA using membrane extract of cysticercus fasciolaris antigen for immunodiagnosis of neurocysticercosis.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] We have used membrane antigen of cysticercus fasciolaris (larval stage of Taenia taeniaeformis pathogenic in rat) in anti-IgG and anti-IgM ELISA for the immunodiagnosis of NC. [5] In the current study, we have designed and evaluated a Dot ELISA using membrane extract of cysticercus fasciolaris antigen for immunodiagnosis of neurocysticercosis.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological tests are more successful with CSF samples, but results are dependent upon the activity of the infection. Inactive cysticerci are usually associated with very low reactivity (162,192). Immunofluorescence and complement fixation (CFA) tests are much less sensitive and specific than ELISA and WB, especially with use of purified antigens (30).…”
Section: Diagnosismentioning
confidence: 99%
“…Rodriguez-Hidalgo et al (2006) analyzed serum of infected swine and obtained high reactivity on 50 and 39-42 kDa protein bands. As reported by Molinari et al (2002), the indirect ELISA results showed that samples from patients with alive cysticercus had higher absorbance than samples from patients whose cysts were calcified or in transitional stages, but this distinction could not be made by immunoblotting. Although different immunodominant proteins were found in the EITB, any band was able to discriminate the different forms of neurocysticercosis.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, the use of this heterologous antigen may contribute for seroepidemiologic studies to evaluate the complex taeniasis/cysticercosis (Vaz et al, 1996;, Sciutto et al, 2000, Ito, 2000. Furthermore, studies have shown that immunoassays were able to detect whether the patients presented alive or inactive cysticerci (Molinari et al, 2002, Barcelos et al, 2005. In order to evaluate and confirm the epidemiological data of neurocysticercosis in the State of Paraná, Brazil, C. longicollis crude extract was used as heterologous antigen of C. cellulosae in ELISA and EITB assay of patients with different (Sotelo et al, 1988) diagnosed through neuroimages features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation